Site engineers manual - Doran, David (Whittles Pub. : CRC Press, 2009)
This is a valuable aide-mémoire and comprehensive pocket handbook for engineers, providing best practice guidance. All aspects of construction are covered from receipt of materials to completion of the finished project.